2022
DOI: 10.1021/acs.orglett.2c01652
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Construction of α,γ-Disubstituted α,β-Butenolides Directly from Allylic Ynoates Using a Chiral Bifunctional Phosphine Ligand Enables Cooperative Au Catalysis

Abstract: A highly efficient construction of chiral γ-substituted α-allyl-α,β-butenolides with up to >99% enantiomeric excess from readily available allylic ynoates is realized. In this asymmetric gold catalysis, the cationic gold­(I) catalyst featuring a bifunctional phosphine ligand enables a four-step cascade which permits the conversion of a diverse array of allylic ynoates into valuable chiral α,γ-disubstituted α,β-butenolides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Thereafter, T. Li, J. Zhu, and L. Zhang reported the application of this ligand for the synthesis of γ-substituted α-allyl-α,β-butenolides ( 11g ) from readily available allylic ynoates ( 11f ) (Scheme 11D). 105 Using L11 ligated gold complex, butenolide derivatives were obtained in excellent enantiomeric excesses (up to >99% ee) and yields (up to 92%). The DFT calculations provided the Gibbs energies for enantiodetermining transition states TS-11C and TS-11D , showing a lower reaction barrier for TS-11C which produces the major enantiomer.…”
Section: Ligand Design For Asymmetric Gold(i) Catalysismentioning
confidence: 99%
“…Thereafter, T. Li, J. Zhu, and L. Zhang reported the application of this ligand for the synthesis of γ-substituted α-allyl-α,β-butenolides ( 11g ) from readily available allylic ynoates ( 11f ) (Scheme 11D). 105 Using L11 ligated gold complex, butenolide derivatives were obtained in excellent enantiomeric excesses (up to >99% ee) and yields (up to 92%). The DFT calculations provided the Gibbs energies for enantiodetermining transition states TS-11C and TS-11D , showing a lower reaction barrier for TS-11C which produces the major enantiomer.…”
Section: Ligand Design For Asymmetric Gold(i) Catalysismentioning
confidence: 99%
“…Scheme 15. Enantioselective isomerization of β,γ-butenolides to chiral α,β-butenolides Additionally, the Zhang group reported that the asymmetric version of ynolates 37 to chiral α-Allyl-α,β-butenolides 38 was achieved with the aid of a (S)-L17-ligated gold catalyst (Scheme 16) [58]. As described, in this tandem reaction, the 'push' and 'pull' processes were involved several times for the generation of an allene intermediate, a furan intermediate and the isomerization product.…”
Section: Bifunctional Phosphine Ligandmentioning
confidence: 99%
“…Very recently, in 2022, Li, Zhu and L. Zhang utilised their previously designed chiral bifunctional phosphine ligand (ent)-L28 for the synthesis of γ-substituted α-allyl α,β-butenolides 41 b from allylic ynoates 41 a, exhibiting an excellent ee of up to > 99 % and yields up to 92 % (Entry 41). [70]…”
Section: Chiral Ligands For Enantioselective Au(i) Catalysismentioning
confidence: 99%